(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article investigates the integration of Artificial Intelligence (AI) in English language teaching (ELT), focusing on its pedagogical implications, advantages, and challenges. The research employs a qualitative content analysis method, examining existing AI-driven tools and recent empirical studies in the domain of language learning. Findings indicate that AI enhances personalized learning, immediate feedback, and learner autonomy, particularly through chatbots, speech recognition, and adaptive testing. However, challenges such as digital literacy gaps and ethical concerns remain. The study underscores the necessity for teacher training and curriculum adaptation to leverage AI’s potential effectively.